2021
DOI: 10.3390/math9182332
|View full text |Cite
|
Sign up to set email alerts
|

Application of Exploratory Factor Analysis in the Construction of a Self-Perception Model of Informational Competences in Higher Education

Abstract: The progress experienced by society resulting from the ready availability of information through the use of technology highlights the need to develop specific learning related to informational competences (IC) in educational settings where future professionals are trained to educate others, specifically in university degrees in social sciences. This study seeks to ascertain the opinions of students enrolled in these degrees at the Universidad de Córdoba (Spain) with regard to the knowledge they consider that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Ordóñez et al (2021) state that the total cumulative variance percentage is one of the decisive criteria in deciding the number of factors to retain. For this study, the total cumulative variance scored 72.02%.…”
Section: Resultsmentioning
confidence: 99%
“…Ordóñez et al (2021) state that the total cumulative variance percentage is one of the decisive criteria in deciding the number of factors to retain. For this study, the total cumulative variance scored 72.02%.…”
Section: Resultsmentioning
confidence: 99%
“…The determinant score was 0.00003077 indicating that an absence of multicollinearity in the data, which made it be suitable for factor analysis [ 53 ]. The Kaiser–Meyer–Olkin value (0.84) indicated that the adequate sampling; the approximate chi-square of the Bartlett’s test of Sphericity of the total scale was 2671.69 with the degrees of freedom ratio 528 (p < 0.001) showed that the data set was worth for a factor analysis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%